Investigation of dynamic characteristics of fused silica hemispherical resonator with shock and harmonic excitation. (30th November 2022) - Chu, Jianning; Liu, Xin; Liu, Changlin; Zhang, Jianguo; Xiao, Junfeng; Chen, Xiao; Xu, Jianfeng
Highlight: Performance parameters testing of a resonator is independent of different excitation methods. All performance parameters of the resonator can be simultaneously measured in a single test. Low-pass filtering of vibration signals does not affect the results of Q factor measurement. The calculation method of the rigid axes angle proposed in this paper can achieve an accuracy of 0.01°. Abstract: The hemispherical resonator is an important component of hemispherical resonator gyro (HRG). The accuracy of resonator performance detection determines HRG service level. In this paper, a method for calculating the rigid axes angle of the resonator is proposed. The reliability of different test methods with shock and harmonic excitations is compared and analyzed. Firstly, a simplified two-dimension spring-mass equivalent modal of the resonator is developed. Secondly, theoretical analysis of the resonator vibration characteristics with different excitations is conducted. The calculation equation of rigid axes angle is next derived. Furthermore, simulation analysis of resonator performance parameters is carried out based on the state space method. Finally, the vibration characteristic testing device of a resonator is established, and the feasibility of the theoretical analysis is verified. Results indicate that the resonator performance parameters are unaffected by different excitation methods. And the proposed calculation method can reach an angle measurement accuracy of 0.01°.